2016
DOI: 10.1177/1744806916665366
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and behavioural characterisation of a mouse model of burn pain identify the cholecystokinin 2 receptor as an analgesic target

Abstract: Burn injury is a cause of significant mortality and morbidity worldwide and is frequently associated with severe and long-lasting pain that remains difficult to manage throughout recovery. We characterised a mouse model of burn-induced pain using pharmacological and transcriptomic approaches. Mechanical allodynia elicited by burn injury was partially reversed by meloxicam (5 mg/kg), gabapentin (100 mg/kg) and oxycodone (3 and 10 mg/kg), while thermal allodynia and gait abnormalities were only significantly imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 63 publications
5
51
0
Order By: Relevance
“…In this study, the administration of proglumide and celecoxib ip reduced formalin-induced nociceptive behavior and tactile allodynia in diabetic rats. These data agree with previous studies that showed proglumide reversed mechanical allodynia but not thermal allodynia in a mouse model of burn pain [Yin et al, 2016]. In addition, L365, 260, and CI-988, selective CCK-2 receptor antagonists reduced mechanical allodynia and thermal hyperalgesia in rats [Kovelowski et al, 2000;Kim et al, 2009].…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the administration of proglumide and celecoxib ip reduced formalin-induced nociceptive behavior and tactile allodynia in diabetic rats. These data agree with previous studies that showed proglumide reversed mechanical allodynia but not thermal allodynia in a mouse model of burn pain [Yin et al, 2016]. In addition, L365, 260, and CI-988, selective CCK-2 receptor antagonists reduced mechanical allodynia and thermal hyperalgesia in rats [Kovelowski et al, 2000;Kim et al, 2009].…”
Section: Discussionsupporting
confidence: 91%
“…A total of 26 rats were used in this study as detailed in Figure . As per the standard practice in transcriptomic analysis, three biological replicates were used for all groups for each of the comparisons made. At study commencement, rats in the body weight range of approximately 80–120 g were used.…”
Section: Methodsmentioning
confidence: 99%
“…The reads were mapped to the Ensembl/Rnor_6.0. Count tables were generated using HTSeq_count from the HTSeq package . Genes were considered to be above the noise level if the read count was ≥ 10.…”
Section: Methodsmentioning
confidence: 99%
“…For example, CCK2R has been confirmed as being expressed in dorsal root ganglion neurons to mediate the inhibition of a Kv current (I A ) to increase pain sensation [16]. The CCK2R antagonist is known to reduce the need for opioid administration in relieving pain in a mouse model of burn-induced pain [17], likely by antagonizing CCK2R-µ-opioid receptor (MOR) heterodimerization, which inhibits MOR signaling [18]. CCK infusion into amygdala in rats has been found to activate a descending CCK2R-mediated pathway and to inhibit spinal neuron discharge, leading to hindpaw analgesia [19].…”
Section: Introductionmentioning
confidence: 99%